On the thermo-mechanical behavior of NiTi shape memory elements for potential smart micro-actuation applications. (August 2016) - Biffi, Carlo A; Bonacina, Luca; Nespoli, Adelaide; Previtali, Barbara; Tuissi, Ausonio
Among smart and functional materials, the shape memory alloys are enabling the development of a new class of devices for the automotive, aerospace, biomedical, and mechanical applications based on the shape memory and superelastic effects. In this work, a study on the mechanical response of NiTi shape memory micro-elements, in the so-called "snake-like" configuration, is reported. These elements were patterned by means of laser micro-processing from thin NiTi sheets and then chemically etched. Different micro-elements, as function of the number of the curvatures replicated, were fabricated and tested. The functional performances of the micro-elements were characterized through calorimetric analysis for the definition of the operating temperatures and through thermo-mechanical testing for the evaluation of their actuating response. Mechanical tests were carried out to assess the tensile behavior of martensite and austenite phases separately, and for evaluating the thermal hysteresis under different constant loads during cooling/heating loops. Moreover, finite element modeling was also accomplished to analyze the stress distribution in both the martensitic and austenitic phases as loading.